Clinical evaluation of GEM 21S(®) and a collagen membrane with a coronally advanced flap as a root coverage procedure in the treatment of gingival recession defects: A comparative study - Singh, Preetinder (Medknow Publications & Media Pvt Ltd, 2012)
AIM: Clinical evaluation of efficacy of rhPDGF-BB plus beta tricalcium phosphate (GEM 21S(®)) along with a collagen membrane in root coverage using a coronally advanced flap. MATERIALS AND METHODS: This human case series evaluated the clinical outcome of rhPDGF-BB with beta-tricalcium phosphate (GEM 21S®) and a collagen membrane in the treatment of recession defects using a coronally advanced flap. Patients were followed postoperatively, and healing was evaluated at 1, 3, and 6 months, with recession depth as the primary outcome measure. RESULTS: This pioneer case series revealed a favorable tissue response to GEM 21S® and collagen membrane from both clinical and esthetic point of view in regenerative periodontal surgery.